League tables exposed - Abd Razak, Dzulkifli (2010)
WHEN the criteria for "worldclass" universities was proposed for Malaysian institutions, I recalled cautioning against the use of ranking. And the rankings have now come back to haunt us! From past experiences, we are acutely aware that such an exercise is far from perfect or desirable from an academic point of view. The Asiaweek ranking folded with the magazine. And the much touted The Times Higher Education Supplement (THES)QS World University Rankings are forced down our throats!